Motivation matters: How enrollment motives shape doctoral experiences and career aspirations - Nikita Smirnov; Elena Tarasova (PLoS ONE, 2025)
This study examines the motivational profiles of Russian doctoral students and their implications for academic success, satisfaction, and career aspirations. We employ data from a nationwide survey of doctoral students at Russian universities (N = 1,267). Using latent class analysis we identify four distinct motivational profiles: Academic Orientation, Unconscious Motives, Topic Devoted, and Everything Everywhere All at Once. Our findings reveal that students with academic orientations exhibit higher satisfaction, greater confidence in successfully defending their dissertations, and a stronger intention to pursue research careers. In contrast, students with unconscious motives demonstrate lower satisfaction, reduced confidence, and a weaker inclination toward research career paths. These findings highlight the role of unclear enrollment goals or non-academic motivations, such as military service deferment, in shaping doctoral outcomes. Additionally, our analysis shows that engagement in research is the only aspect of the doctoral experience that fosters research career aspirations among students with initially non-academic motivations. These findings emphasize the need for Russian universities to reconsider admission policies, doctoral program structures, and academic support mechanisms to better accommodate the increasingly diverse expectations of doctoral students. The study contributes to the broader discourse on doctoral education by providing empirical insights into the relationship between motivation, institutional factors, and career trajectories.